Pre-Service Teachers’ Online Learning Experience – Challenges and Lessons Learned - Beka, Arlinda; Bicaj, Arberore (Pedagogika, 2025)
This study aims to investigate the impact of the COVID-19 lockdown on the professional growth of pre-service teachers in adapting to virtual learning. It examines the experiences of 421 University of Prishtina pre-service teachers using a mixed-methods approach. Despite technical challenges, the results indicate increased peer collaboration. The study emphasizes the importance of raising the quality of online education in order to better prepare for emergencies in the future.